Life Storytelling across Media and Contexts (Narrative Inquiry)

60-Gb/s 1:4 Demultiplexer in 22-nm FD-SOI Technology Using TSPC Logic: A Circuit-to-System-Level Analysis and Design - Sadiye, Babak; Iftekhar, Mohammed; Müller, Wolfgang; Scheytt, J. Christoph (IEEE Transactions on Very Large Scale Integration (VLSI) Systems)

Synthesis of Amidines Via P(III)/P(V)=O Redox Catalyzed In Situ Formation of Imidoyl Chlorides From Amides - Medvaric, Viktorija; Paradies, Jan; Werner, Thomas (Advanced Synthesis and Catalysis)
Amidines are a ubiquitous class of bioactive compounds found in a wide variety of natural products; thus, efficient strategies for their preparation are in great demand. Herein, a novel protocol is reported for the synthesis of amidines based on P III /P V O redox catalysis. This two‐step, one‐pot approach involves the activation of amides via P III /P V O catalyzed in situ formation of imidoyl chloride intermediates which are directly converted upon reaction with amines into the corresponding amidines. Instead of traditionally used toxic and corrosive chloride sources, hexachloroacetone (HCA) is successfully employed as a halide source. The reaction proceeds with low catalyst loading (2 mol%) in BuOAc as the solvent. Under the optimized conditions, 20 amidines are prepared in yields up to 99%. A feasible mechanism is proposed based on experimental results. The synthetic potential of this method is evaluated in the preparation of the tyrosine kinase inhibitor (TKI) Erlotinib.
Keywords: T2; T; CSSD

Straightforward Access to Terpene-Based 1,2-Diols and Their Acetals as Fragrance Ingredients - Stefanow, Vivian; Kell, Lukas; Leduskrasta, Aiga; Eh, Marcus; Panten, Johannes; Werner, Thomas (The Journal of Organic Chemistry)
Keywords: T4; CSSD

Metal-Free Reduction of Nitrous Oxide via PIII/PV═O Cycling: Mechanistic Insights and Catalytic Performance - Zhou, Rundong; Medvaric, Viktorija; Werner, Thomas; Paradies, Jan (Journal of the American Chemical Society)
Keywords: T2; CSSD

Spatio-spectral diarization of meetings by combining TDOA-based segmentation and speaker embedding-based clustering - Cord-Landwehr, Tobias; Gburrek, Tobias; Deegen, Marc; Haeb-Umbach, Reinhold (Proceedings of INTERSPEECH)
We propose a spatio-spectral, combined model-based and data-driven diarization pipeline consisting of TDOA-based segmentation followed by embedding-based clustering. The proposed system requires neither access to multi-channel training data nor prior knowledge about the number or placement of microphones. It works for both a compact microphone array and distributed microphones, with minor adjustments. Due to its superior handling of overlapping speech during segmentation, the proposed pipeline significantly outperforms the single-channel pyannote approach, both in a scenario with a compact microphone array and in a setup with distributed microphones. Additionally, we show that, unlike fully spatial diarization pipelines, the proposed system can correctly track speakers when they change positions.

Continuous value shaping: A boundary concept for innovating service innovation approaches - Böhmann, Tilo; Roth, Angela; Satzger, Gerhard; Benz, Carina; Beverungen, Daniel; Boes, Andreas; Breidbach, Christoph; Gersch, Martin; Gudergan, Gerhard; Hogreve, Jens; Kurtz, Christian; Langes, Barbara; et al. (Electronic Markets)
Technological advancements and evolving value orientations reshape future value creation and pose new requirements for service innovation. While a variety of disciplines are developing new approaches to drive service innovation, this is primarily done in isolation and generates only fragmented solutions. Sociological theory has proposed “boundary objects” as an effective umbrella for communication and cooperation among communities. Therefore, we introduce continuous value shaping (CVS) as a boundary object describing service innovation approaches along five principles. We reflect on this concept through the different disciplinary lenses of researchers in service marketing, information systems, service engineering, sociology of work, and innovation management. These perspectives highlight how the CVS principles already connect to discourses within the individual disciplines. However, the CVS concept will not only provide an umbrella to embrace existing activities in different academic disciplines. It also assists to identify research themes that will benefit from uniting the power of these disciplines, and it can serve as an integrating framework to conceptualize complex service innovation approaches. Thus, the CVS concept should guide both researchers and practitioners to develop and implement novel innovation and transformation efforts—in and across organizations.
Keywords: Continuous value shaping (CVS); Service research; Service innovation; Digitalization; Sustainability; Interdisciplinary research

Deeper down the rabbit hole - How technology conspiracy beliefs emerge and foster a conspiracy mindset - Trang, Simon Thanh-Nam; Krämer, Tobias; Trenz, Manuel; Weiger, Welt (Information Systems Research (VHB Jourqual 3 A+, FT50))

Don’t count your chickens before they hatch: Conceptualizing and exploring deviations from polls during public health app releases - Trang, Simon Thanh-Nam; Trenz, Manuel; Welf, Weiger (Journal of Information Technology)

A field experiment on ISP training designs for enhancing employee information security compliance - Nastjuk, Ilja; Rampold, Florian; Trang, Simon Thanh-Nam; Benitez, Jose (European Journal of Information Systems (VHB Jourqual 3 A))

Motivational Framing Strategies in Health Care Information Security Training: Randomized Controlled Trial - Keller, Thomas; Warwas, Julia; Klein, Julia; Henkenjohann, Richard; Trenz, Manuel; Trang, Simon Thanh-Nam (JMIR Medical Education)

Better (Cyber) Insured than Sorry? Unraveling Cognitive Factors in the (Non-)Adoption of Personal Cyber Insurance using fsQCA - Schütz, Florian; Ortiz de Guinea Lopez, Ana; Wolf, Tobias; Trang, Simon Thanh-Nam (Communications of the Association for Information Systems)

Keep Reward Or Return Fee – How Do Incentives In Product Return Management Influence Return Decisions And Future Customer Behavior? - Horsthemke, Johanna; Böhm, Eva (Proceedings of the 2025 AMS 25th World Marketing Congress)

Large‐Scale Interlaboratory Study Along the Entire Process Chain of Laser Powder Bed Fusion: Bridging Variability, Standards, and Optimization across Metals and Polymers - Kuşoğlu, Ihsan Murat; Garg, Sunidhi; Abel, Arvid; Balachandran, Prasanna V.; Barcikowski, Stephan; Becker, Louis; Bernsmann, Jan-Simeon; Boseila, Jonas; Broeckmann, Christoph; Coskun, Mert; Dreyer, Malte; East, Mark; et al. (Advanced Engineering Materials)
Laser powder bed fusion is a cornerstone technology for additive manufacturing (AM) of metals and polymers, yet challenges in achieving consistent reproducibility and process optimization persist. Addressing these requires a systematic understanding of the interactions between feedstock, process parameters, and final part characteristics throughout the entire production chain. This study presents results from a comprehensive interlaboratory investigation conducted by 32 research institutions, evaluating six feedstock, including nanoparticle‐modified aluminum alloy and polyamide powders, under standardized protocols. Data analysis encompasses 69 powder properties, 15 process parameters per print, and 78 part features, culminating in a dataset of over 1.2 million correlations. Advanced statistical methods and machine learning are employed to identify critical variability drivers, such as the impact of nanoparticle modifications on powder flowability and thermal conductivity, as well as the influence of process parameters on reproducibility. Newly introduced dimensionless figures of merit provide universal metrics to describe and predict thermal and mechanical interactions, simplifying process optimization and material characterization. The findings, supported by an open‐access dataset adhering to findable, accessible, interoperable, and reusable principles, advance understanding of material–process–structure–property relationships. They establish a benchmark for future research and lay the foundation for improving the reliability, quality, and sustainability of AM processes.

The importance of structure in transformation chaos: A Transformation Framework - Gräßler, Iris; Grewe, Benedikt; Fritzen, Marc (AHFE International)
Dynamic market conditions, technological disruption and social change require organizations to continuously adapt and evolve. However, studies on organizational change show that the majority of transformations undertaken fail because they are characterized by a lack of clarity, overload and ineffective measures. This paper shows how a clear structure as a critical success factor can make the chaos and challenges of a transformation manageable. The focus here is on a practice-oriented framework that divides a transformation into nine essential building blocks with activities that are critical to success. The structure of the framework is understood as a flexible organizing principle for a transformation without hindering creativity and dynamics. Case studies show the adaptability and applicability of the framework to different characteristics and dimensions of transformation. The transformation framework provides an operative structure and enables transformation managers for transparent orchestration and implementation of transformation.

Data-driven decision support in the design and controlling of systems engineering transformation: a maturity model - Graessler, Iris; Grewe, Benedikt; Felgen, Luc (Proceedings of the Design Society)
ABSTRACT: Challenges of increasing system complexity and the need for interdisciplinary collaboration are prompting companies to reorganize towards Systems Engineering (SE). As part of the implementation of large-scale transformation programs, transformation progress is of great interest to management and employees involved. Existing maturity models lack measurable variables and reliable forecast. For this reason, a maturity model for evaluating SE Transformation is developed, that builds on quantitative metrics and enables an overarching view on transformation considering cultural aspects. Literature-based criteria for evaluating SE Transformation lay the foundation for measures and referenced metrics and indicators. Due to its data-centricity, the model presented enables a more comprehensive, fact-based decision-making basis for the design and steering of SE Transformation programs.

SETup automotive: a Method for Systems Engineering Transformation in automotive industry - Graessler, Iris; Grewe, Benedikt (Design Science)
Abstract The increasing prevalence of embedded software in today’s vehicles is leading to growing complexity, which can only be managed effectively through the use of reliable interdisciplinary engineering processes. With this in mind, systems engineering (SE) is currently being introduced on a large scale into the automotive industry. Pilot projects have demonstrated the potential for implementing changes, but these have not yet been accompanied by viable implementation concepts for SE. In the context of the proposed application-based research, the SETup automotive method ( S ystems E ngineering T ransformation u nder p iloting in the automotive industry) is presented, which comprises a step-by-step procedure of introducing SE into large automotive companies. By introducing SE by pilot projects first, both an in-process tailoring of all processes, methods, tools and structures (PMTS) required for the introduction and an in-process validation of the pilot scheme elaborated by the pilot projects are achieved. The presented method builds upon fundamental approaches to change management, which have been developed over many years in both research and practice. It has been validated by the industrial practice of SE transformation at German car manufacturers and suppliers. As a result, decision-makers, transformation managers and systems engineers are provided with a scientifically based and field-tested set of steps for the introduction of SE in their own company.

Strategic Product Planning Model – Digital twins for circular products and production processes - Gräßler, Iris; Rarbach, Sven; Grewe, Benedikt (Industry 4.0 Science)

Model-based Impact Analysis for Engineering Sustainable Products in Value Creation Networks - Gräßler, Iris; Rarbach, Sven (Procedia CIRP)

Structuring Systems Engineering Transformation: A three-step cycle of Transformation - Gräßler, Iris; Grewe, Benedikt (Procedia CIRP)